Isotope Dilution DNA Logic Circuits for Multiple Output and Absolute Quantification - Zhu, Yiyan; Wei, Chao; Li, Ziyan; Li, Yan; Liu, Rui; Lv, Yi (Analytical chemistry (Washington), 2025)
DNA logic circuits have gained great success in the past, thanks to their distinct performance regarding the scalability and correctness of computation. However, there are still two challenges often considered for DNA logic circuit-based computation. First, the mainstream optical probes are often subject to spectral overlapping interference for complex multitask analysis and outputs. Second, absolute quantification results traceable to the primary international system of units are mission impossible, especially for interlaboratory comparisons and quality assurances. Herein, we constructed DNA logic circuits encoded with lanthanide isotopes and decoded by elemental mass spectrometry. The 155Gd-enriched isotope and 145Nd-enriched isotope were incorporated in the DNA logic circuits for the isotope dilution-based absolute quantification of microRNAs. The proposed isotopic DNA logic circuits greatly enhance the multiplexity and computation accuracy, which poses a great potential for cancer biomarker-related diagnosis.